2004
DOI: 10.1111/j.1365-2036.2004.02183.x
|View full text |Cite
|
Sign up to set email alerts
|

Review article: epidemiology and quality of life in functional gastrointestinal disorders

Abstract: SUMMARYThe epidemiology and health-related quality of life associated with functional gastrointestinal disorders are reviewed, with particular emphasis on irritable bowel syndrome and functional dyspepsia. The literature supports the significant world-wide prevalence of functional gastrointestinal disorders, including irritable bowel syndrome (IBS), functional dyspepsia and chronic constipation. An increased female prevalence has been demonstrated in most studies in patients with IBS and chronic constipation, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
224
7
7

Year Published

2009
2009
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 299 publications
(245 citation statements)
references
References 74 publications
(69 reference statements)
7
224
7
7
Order By: Relevance
“…Functional digestive disorders are considered to represent up to 50% of medical consultations in gastroenterology (3,4), and epidemiological studies suggest that there is a considerable overlap between these disorders (5).…”
Section: Introductionmentioning
confidence: 99%
“…Functional digestive disorders are considered to represent up to 50% of medical consultations in gastroenterology (3,4), and epidemiological studies suggest that there is a considerable overlap between these disorders (5).…”
Section: Introductionmentioning
confidence: 99%
“…Significantly higher absolute intakes of beta-carotene were seen in Healthy, while 219 fibre intakes were very similar in Healthy and Convenience. Additional analysis investigating 220 nutrient intake per 1000 kcal revealed that higher intakes were seen in Healthy, significantly soM A N U S C R I P T 9 for protein, fibre, vitamin A, beta-carotene, niacin, vitamin B 6 , folate, vitamin B 12 , vitamin E, 222 iron, magnesium, potassium, sodium and vitamin C, supporting the characterization that this 223 cluster was the healthier cluster with a more nutrient dense dietary intake (data not shown). 224…”
Section: Results 172mentioning
confidence: 96%
“…In addition, direct and indirect economic stress due to FD was found to be high and also has considerable impact on productivity. The health related quality of life is impacted significantly in patients with FD when compared to general healthy population [6,7]. A disturbance in gastric emptying has been reported to be a major pathophysiological mechanism of FD [1].…”
Section: Discussionmentioning
confidence: 99%